Sarana Dan Prasarana Kantin SMP Negeri 40 Jakarta Sebagai Penunjang Program Kantin Sehat Berstandar Adiwiyata - Sephia Ananda Putri; Desy Safitri; Saipiatuddin Saipiatuddin (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
Canteen facilities and infrastructure is an important component in efforts to support school health so it needs to be considered in accordance with adiwiyata standards. Things to consider include; canteen construction, sanitation facilities, pest and insect control, as well as kitchens, cooking and food equipment and supplies. SMP Negeri 40 Jakarta is one of the schools that implements a healthy canteen. The purpose of this study was to provide an overview or describe the facilities and infrastructure of healthy canteen implemented by SMP Negeri 40 Jakarta. The type of research used in this study is a descriptive method with a quantitative approach. included in the good categorization with the percentage of accumulated data by 75%. This shows that the school facilitates canteen facilities and infrastructure well. Based on the results of the study, it is known that there are several indicators of canteen sanitation facilities that are in poor condition. In addition, there are still traders who lack awareness in accommodating food that is not in accordance with standards.